Methods of conducting field experiments in hillylands - Gomez, Arturo A. (Philippine Agricultural Scientist, The (Formerly the Philippine Agriculturist), 2000)
Research methods of field experiments in the hillylands must address the following important features: a) wide variations among experimental plots; b) even wider variations among plots and among farms; c) measurement procedures that are inexpensive and allow for a much larger number of samples; and d) replications. The above are particularly important for evaluating soil and water loss whose measurements are associated with higher errors. Examples of procedures for measuring soil loss, evaluating sustainability, and conducting on-farm trials are presented.